A Year Inland : The Journal of a Hudson's Bay Company Winterer - Henday, Anthony, fl. 1748-1755 (Book collections on Project MUSE., 2000)
Anthony Henday, a young Hudson's Bay Company employee, set out from York Factory in June 1754 to winter with "trading Indians" along the Saskatchewan River. He adapted willingly and easily to their way of life; he also kept a journal in which he described the plains region and took note of rival French traders, and success at their inland posts. A copy of Henday's journal was immediately sent to the company directors in London. They rewarded Henday handsomely although they were uncertain where he had travelled, what groups he had met on the plains, and what success he had in opposing rival French traders. Since then, uncertainty about Henday's year inland has increased. The original journal disappeared; only four copies, dating from 1755 to about 1782, are extant. Each text differs from the other three; the differences range from variant spellings to word choice to contradictory statements on vital questions. All four copies are the work of a company clerk, later factor, named Andrew Graham, who used them to support his own views on HBC trading policies. Twentieth-century scholars have based their claims for Henday's importance as an explorer, trader and observer of Native cultures on a poorly edited transcript of the 1782 text. They have been unaware or careless of the journal's textual ambiguity. A Year Inland presents all four copies for the first time, together with contextual notes and a commentary that reassesses the journal's information on plains geography, people and trade.